Pemberian Buah Pepino (Solanum Muricatum Aiton) Terhadap Perubahan Tekanan Darah Pada Wanita Menopause Dengan Hipertensi Primer - Setyarini, Didien Ika; Kinasih, Heni Tirta (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2021)
Menopause is a cycle that all women will experience. During menopause, many symptoms are associated with reduced estrogen production. Menopause also affects cholesterol levels, causing an increase in LDL, which can narrow and clog arteries so that blood flow becomes blocked and consequently increases blood pressure. This study aims to determine the effect of giving pepino fruit to changes in blood pressure in postmenopausal women with primary hypertension. The design used is a pre-experiment with a one group pre test post test design. The total population is 26 postmenopausal women aged 45-60 years. This study used purposive sampling technique and obtained a sample of 21 respondents. Respondents who entered the inclusion criteria were given the treatment of giving pepino fruit for each rice to be consumed after breakfast for 7 consecutive days. The instruments used to collect data are mercury sphygmomanometer and questionnaire. The results showed that there was a decrease in systolic blood pressure by 62.5% and diastolic blood pressure by 74.2%. The results of the statistical paired t-test with a significant level of 0.05 and dk = 20 have obtained t-count > t-table (systole = 8.05> 1.72 and diastole = 8.22> 1.72) there is an effect administration of pepino fruit on changes in blood pressure in postmenopausal women with primary hypertension. Purple pepino fruit contains potassium which can lower blood pressure by blocking calcium channels. Thus, health workers are expected to pay more attention to the health of postmenopausal women by means of early detection, counseling and treatment of hypertension. Keywords: The effect of Pepino Fruit, Blood Pressure, Menopause